2020
DOI: 10.1007/s40201-020-00452-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel Escherichia coli O157:H7-specific phage as a biocontrol agent

Abstract: Purpose Escherichia coli O157:H7 is one of the major foodborne pathogens of global public concern. Bacteriophages (phages) have emerged as a promising alternative to antibiotics for controlling pathogenic bacteria. Here, a lytic E. coli O157:H7-specific phage (KFS-EC) was isolated, identified, and characterized to evaluate its potential as a biocontrol agent for E. coli O157:H7. Methods KFS-EC was isolated from slaughterhouse in Korea. Morphological analysis, genomic analysis and several physiological tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 60 publications
3
11
0
Order By: Relevance
“…Moreover, at the end of culture, the emergence of BIMs was observed at low MOIs (0.01 and 0.1) but not at high MOIs (1 and 10). These results were similar to those of recently reported E. coli O157:H7 infecting myophage KFS-EC; however, KFS-EC caused the BIMs, even at a relatively high MOI of 100, unlike BECP10 [ 52 ]. In addition, both phage ECP26 and BECP10 did not significantly affect the pH of bacterial culture ( Figure S1 ).…”
Section: Resultssupporting
confidence: 91%
“…Moreover, at the end of culture, the emergence of BIMs was observed at low MOIs (0.01 and 0.1) but not at high MOIs (1 and 10). These results were similar to those of recently reported E. coli O157:H7 infecting myophage KFS-EC; however, KFS-EC caused the BIMs, even at a relatively high MOI of 100, unlike BECP10 [ 52 ]. In addition, both phage ECP26 and BECP10 did not significantly affect the pH of bacterial culture ( Figure S1 ).…”
Section: Resultssupporting
confidence: 91%
“…Taken together, the results of the pH-inactivation assay suggested that VR26 sustained its lytic property through a broad range of pHs, indicating greater stability of this phage compared with other O26:H11-infecting [ 24 ] or even O157:H7-infecting viruses [ 24 , 35 , 36 , 37 ] described in previous studies.…”
Section: Resultssupporting
confidence: 64%
“…Foodborne illnesses caused by E. coli O157:H7, Salmonella, or Shigella are of great concern to public health. Lytic phages as biocontrol agents have garnered growing interest due to their bacterial lytic, physiologically robust, safe, and eco-friendly properties [20,45,46]. For developing a phage-based biocontrol agent, phage effectiveness should be ensured prior to its employment [47].…”
Section: Discussionmentioning
confidence: 99%